1997
DOI: 10.1111/j.1600-079x.1997.tb00322.x
|View full text |Cite
|
Sign up to set email alerts
|

The validity of melatonin as an oncostatic agent

Abstract: The validity of melatonin as an oncostatic agent Panzer A, Viljoen M. The validity of melatonin as an oncostatic agent. J. Pineal Res. 1997; 22: 184-202. 0 Munksgaard, Copenhagen Abstract: The validity of melatonin as a prominent, naturally occurring oncostatic agent is examined in terms of its putative oncostatic mechanism of action, the correlation between melatonin levels and neoplastic activity, and the outcome of therapeutically administered melatonin in clinical trials. Melatonin's mechanism of action is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 130 publications
1
58
0
Order By: Relevance
“…Moreover, MEL is a potent scavenger of reactive oxygen species and an antioxidant (Reiter et al, 1998(Reiter et al, , 2000Ng et al, 2000); and, together with its metabolites, some of which may be more potent than MEL (Ng et al, 2000), MEL appears to protect tissues against oxidative stress (Ng et al, 2000;Reiter et al, 2000). There have been suggestions from laboratory studies and clinical trials that MEL may also possess neuroprotective (Thomas and Mohanakumar, 2004), cardioprotective (Chen et al, 2003), and anticancer (Panzer and Viljoen, 1997) properties. MEL has been evaluated as a therapeutic agent in a number of conditions, including sleep disturbance, jet lag, and metastatic cancer (Lissoni et al, 1989;Herxheimer and Petrie, 2002;Singer et al, 2003).…”
mentioning
confidence: 99%
“…Moreover, MEL is a potent scavenger of reactive oxygen species and an antioxidant (Reiter et al, 1998(Reiter et al, , 2000Ng et al, 2000); and, together with its metabolites, some of which may be more potent than MEL (Ng et al, 2000), MEL appears to protect tissues against oxidative stress (Ng et al, 2000;Reiter et al, 2000). There have been suggestions from laboratory studies and clinical trials that MEL may also possess neuroprotective (Thomas and Mohanakumar, 2004), cardioprotective (Chen et al, 2003), and anticancer (Panzer and Viljoen, 1997) properties. MEL has been evaluated as a therapeutic agent in a number of conditions, including sleep disturbance, jet lag, and metastatic cancer (Lissoni et al, 1989;Herxheimer and Petrie, 2002;Singer et al, 2003).…”
mentioning
confidence: 99%
“…Therefore, a combination could effectively lower the threshold for chemoagents, protect normal tissues from being sensitized to the cytotoxicity of these therapies, and reduce side effects via its free radical scavenging/antioxidant properties (7). In most of the combination trials where melatonin was used in conjunction with therapeutic drugs, the presence of melatonin was found to prolong disease progression-free time and overall survival as well as improve patient suffering (3,30). For example, in a noteworthy study, Lissoni et al (31) evaluated the effects of concomitant melatonin administration on toxicity and efficacy of several chemotherapeutic combinations in advanced cancer patients with poor clinical status.…”
Section: Melatonin In Adjuvant Settingsmentioning
confidence: 99%
“…In addition to its interactions with these physiologic systems, melatonin also displays several other biological properties, including a. direct quenching effect on oxygen free radicals, which we have previously described (Zang et ah, 1998). More importantly, melatonin treatment substantially decreases tumor development in animal models of breast cancer (Bojkova et ai, 2000;Teplitzky et al, 1999) and has been suggested as a naturally occurring oncostatic agent in humans (Cos and Sanchez-Barcelo, 2000b;Panzer and Viljoen, 1997). Tissue and serum levels of melatonin are significantly and inversely related to nuclear grade of human breast malignancy (Maestroni and Conti, 1996), and excretion of melatonin metabolites has been shown to be decreased in breast cancer patients and to be negatively correlated with tumor size (Bartsch and Bartsch, 1999).…”
Section: Academic Pressmentioning
confidence: 99%